2009
DOI: 10.1007/s11046-009-9251-3
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Investigation of Antifungal Activity of Allicin Alone and in Combination with Azoles Against Candida Species

Abstract: Candidiasis is a term describing infections by yeasts from the genus Candida, and the type of infection encompassed by candidiasis ranges from superficial to systemic. Treatment of such infections often requires antifungals such as the azoles, but increased use of these drugs has led to selection of yeasts with increased resistance to these drugs. In this study, we used allicin, an allyl sulfur derivative of garlic, to demonstrate both its intrinsic antifungal activity and its synergy with the azoles, in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 34 publications
5
38
0
Order By: Relevance
“…Those in the latter group include pyrimidine analogues, thymidylate synthase inhibitors, and mitotic inhibitors [6]. However, treatment of C. albicans infections with these drugs may lead to side effects such as hepatotoxicity and nephrotoxicity [7], resistance, and frequent recurrence. For these reasons, treatment using home remedies has been widely introduced worldwide, and new antifungal agents from natural resources are being studied intensively.…”
Section: Introductionmentioning
confidence: 99%
“…Those in the latter group include pyrimidine analogues, thymidylate synthase inhibitors, and mitotic inhibitors [6]. However, treatment of C. albicans infections with these drugs may lead to side effects such as hepatotoxicity and nephrotoxicity [7], resistance, and frequent recurrence. For these reasons, treatment using home remedies has been widely introduced worldwide, and new antifungal agents from natural resources are being studied intensively.…”
Section: Introductionmentioning
confidence: 99%
“…Sohn et al [14] reported antifungal activity of the prominent compound, fistulosides from A. fistulosum, with the MIC ranged from 3.1 to 6.2 μg/ml and the MFC ranged from 3.1 to 6.2 μg/ml. Khodavandi et al [12] used allicin to demonstrate its intrinsic antifungal activity, and the MIC of allicin against six Candida species ranged from 0.05 to 25 μg/ml. Aala et al [11] evaluated the in vitro efficacy of pure allicin alone against six dermatophyte isolates, and the MIC ranged from 0.098 to 25.0 μg/ml.…”
Section: Antifungal Activity Of Taiwanese a Fistulosummentioning
confidence: 99%
“…Yamada and Azuma [3] studied the antifungal activity of allicin by using the agar dilution methods in Sabouraud glucose medium, in which the MIC of allicin against Candida, Cryptococcus, Ttichophyton, Epidermophyton, and Microsporum ranged from 3.13 to 25.0 μg/ml. Khodavandi et al [12] investigated the antifungal activity of allicin against Candida species, and the MIC of allicin alone against six Candida species within the range of 0.05 -25 μg/ml. Aala et al [11] evaluated the in vitro efficacy of pure allicin alone against six dermatophytes, and the MIC of allicin ranged from 0.098 to 25.0 μg/ml.…”
Section: Relationship Between Allicin Content and Antifungal Activitymentioning
confidence: 99%
“…Adhesion of Candida spp. to buccal epithelial cells was signifi cantly reduced after both short and long time exposure to aqueous garlic extract (Ghannoum 1988 (Khodavandi et al 2010 ). However, when allicin was used in combination with fl uconazole or ketoconazole, the MICs were decreased in some isolates.…”
Section: Antifungal Activitymentioning
confidence: 99%